25th anniversary article recent advances in n-type and ambipolar organic field-effect transistors - Zhao, Yan (Advanced materials (Deerfield Beach, Fla.), 2013)
Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.